Protecting sticky consumers in essential markets - Walter Beckert; Paolo Siciliani (Institute for Fiscal Studies (IFS), 2021)
This paper studies regulatory policy interventions aimed at protecting sticky consumers who are exposed to exploitation. We model heterogeneous consumer switching costs alongside asymmetric market shares. This setting encompasses many markets in which established firms are challenged by new entrants. We identify circumstances under which such interventions can be counterproductive, both with regard to the stated consumer protection objective and the complementary aim to promote competition.
Keywords: L11; L13; D4; 330; switching costs; price discrimination; uniform pricing; most-favoured customer clauses; price regulation; competition